Preclinical efficacy of the novel competitive NAMPT inhibitor STF-118804 in pancreatic cancer - Espindola-Netto, Jair Machado (Oncotarget, 2017)
NAD salvage is one of the pathways used to generate NAD in mammals. Nicotinamide phosphoribosyltransferase (NAMPT), the rate-limiting enzyme in this pathway, uses nicotinamide (NAM) to generate nicotinamide mononucleotide (NMN). NMN is one of the main precursors of NAD synthesis in cells. Our previous study showed the importance of NAMPT in maintaining NAD levels in pancreatic ductal adenocarcinoma cells (PDAC), and that the NAMPT inhibitor FK866 decreased pancreatic cancer growth. We now tested the effect of STF-118804, a new highly specific NAMPT inhibitor, in models of pancreatic ductal adenocarcinoma. STF-118804 reduced viability and growth of different PDAC lines, as well as the formation of colonies in soft agar. In addition, STF-118804 decreased glucose uptake, lactate excretion, and ATP levels, resulting in metabolic collapse. STF-118804 treatment activated AMPK and inhibited of mTOR pathways in these cells. This effect was significantly potentiated by pharmacological AMPK activation and mTOR inhibition. Exogenous NMN blocked both the activation of the AMPK pathway and the decrease in cell viability. Panc-1 cells expressing GFP-luciferase were orthotopically implanted on mice pancreas to test the in vivo effectiveness of STF-118804. Both STF-118804 and FK866 reduced tumor size after 21 days of treatment. Combinations of STF-118804 with chemotherapeutic agents such as paclitaxel, gemcitabine, and etoposide showed an additive effect in decreasing cell viability and growth. In conclusion, our preclinical study shows that the NAMPT inhibitor STF-118804 reduced the growth of PDAC in vitro and in vivo and had an additive effect in combination with main current chemotherapeutic drugs.